Hubungan antara Sibling Rivalry dan Pola Asuh Otoriter dengan Motivasi Berprestasi pada Mahasiswa - Octavia, Firda; Ruby, Arcivid Chorynia (Universitas Mathla'ul Anwar Banten, 2025)
This study aims to examine the relationship between sibling rivalry and authoritarian parenting style with achievement motivation among university students. The participants in this study were 80 active students from a university in Kudus City, selected through purposive sampling. The research instruments used included a sibling rivalry scale, an authoritarian parenting style scale, and an achievement motivation scale. The results showed that the correlation coefficient between the three variables (rx1,2) was 0.356 with a significance level of p = 0.005 (p < 0.01), and an effective contribution of 12.7%. This indicates a highly significant relationship between sibling rivalry (X1) and authoritarian parenting style (X2) with achievement motivation (Y). The first minor hypothesis test revealed a significant negative relationship between sibling rivalry and achievement motivation, with a correlation coefficient of rx1y of -0.239 and a p-value of 0.032 (p < 0.05). The second minor hypothesis test also indicated a highly significant negative relationship between authoritarian parenting style and achievement motivation, with a correlation coefficient of rx2y of -0.343 and a p-value of 0.002 (p < 0.01). Based on these findings, it can be concluded that there is a significant negative relationship between the variables. Both sibling rivalry and authoritarian parenting style are negatively associated with students’ achievement motivation.